2018
DOI: 10.2528/pier18041707
|View full text |Cite
|
Sign up to set email alerts
|

Layer-to-Layer Angle Interlock 3d Woven Bandstop Frequency Selective Surface

Abstract: A flexible fully textile-integrated bandstop frequency selective surface working at a central frequency of 3.75 GHz and presenting a 0.6 GHz bandwidth has been designed, manufactured and experimentally characterised. The frequency selective surface consists of a multilayered woven fabric whose top layer presents periodic cross-shaped conductive resonators, and due to its symmetries, its performance is largely independent of polarisation and angle of incidence. These properties make the prototype very interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…7, there is a slight frequency difference between CT FSS and CY FSS, while transmission coefficients are acceptable (under -10 dB) in both. This also accords with the researchers' earlier observations, which showed that there are differences between simulation/copper and textile FSS [10,50,51].…”
Section: Measurement Results Of Fsssupporting
confidence: 93%
“…7, there is a slight frequency difference between CT FSS and CY FSS, while transmission coefficients are acceptable (under -10 dB) in both. This also accords with the researchers' earlier observations, which showed that there are differences between simulation/copper and textile FSS [10,50,51].…”
Section: Measurement Results Of Fsssupporting
confidence: 93%
“…At a specific frequency, the absorption peak was greater than 90%, and it had a good deformation effect, which can be easily worn on the body. Alonso-gonzalez et al [85] fabricated a kind of frequencyselective surface 3D woven fabric, in which conductive yarns were woven into a cruciform frequency-selective surface. Due to the symmetry of surface, wave absorption performance was largely independent of polarization and incident Angle, which can achieve large broadband wave absorption.…”
Section: Researches Of Wave-absorbing Fabrics Preparationmentioning
confidence: 99%
“…Researchers at the University of Sheffield developed knitted textile FSS [26]. A threedimensional u-shaped FSS unit cell is investigated in [27] whereas, layer to layer angle interlock 3D woven bandstop FSS is realized in [28].…”
Section: Introductionmentioning
confidence: 99%